THE FIGHT AGAINST MONEY LAUNDERING AND TERRORISM FINANCING: THE PORTUGUESE EXPERIENCE - Conceição, Ana Raquel; Piton, André Paulino (Novos Estudos Jurídicos, 2021)
Contextualização do tema:When it comes to investigating terrorism and, consequently, money laundering, the consideration of balancing the defence of rights and liberties becomes less stringent in the eyes of States. They tend to automatically replace community or the collective interest. It is, therefore, important to question if the weighting and balancing result from the legal text. Objetivos: One of the legal instruments is Act 83/2017, of August 18th, and we will review its regime by introducing its main measures and assessing the (dis)respect for fundamental rights. Metodologia: For the development of the research, the inductive method was used from the literature review. Resultados: The number of entities and duties leads us to conclude that States, without any doubt, cannot fight these crimes on their own. They must unite, apply measures that can produce effects in every country, but even when doing so, they need their citizens to help them in this fight; such citizens are those that deal with financing activities, those who deal with criminals themselves or even those with relation to people that have political or economic power.